2018
DOI: 10.4155/fsoa-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Matrix Metalloproteinases 1–3 and Their Inhibitor are Not Associated With Premature Labor

Abstract: Aim:Extracellular matrix metalloproteinases (MMPs) and their inhibitors (tissue inhibitors of metalloproteinases [TIMPs]) are involved in the breakdown of fetal membranes before delivery. Our aim was to investigate the occurrence of any polymorphism on genes coding for MMPs 1-3 and TIMP 2 in preterm laboring patients as a potential source of this phenomenon. This question has not been studied before.Methodology & results:A prospective population study was performed in a Greek university hospital. Group A (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This can lead to amniotic fluid leakage, increasing the risk of fetal membrane infection and premature birth. AFC are an important component in maintaining the strength and elasticity of fetal membranes [ 28 ], and the early or excessive maturation of AFC can affect the stability of membranes. The functional assay of AFC after stimulation with PROZ illustrated that the PROZ concentration is positively associated with AFC proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to amniotic fluid leakage, increasing the risk of fetal membrane infection and premature birth. AFC are an important component in maintaining the strength and elasticity of fetal membranes [ 28 ], and the early or excessive maturation of AFC can affect the stability of membranes. The functional assay of AFC after stimulation with PROZ illustrated that the PROZ concentration is positively associated with AFC proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Fujimoto et al explored the same variant and found a significant association between fetal carriage of the 2G allele and preterm premature rupture of membranes [27]. In another study, Lathouras et al reported that different polymorphisms of MMP-1, -3 and TIMP-2 were not associated with premature labor [28].…”
Section: Discussionmentioning
confidence: 99%
“…The studied polymorphisms were genotyped through polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques. The primers and restriction enzymes (Thermo Fisher Scientific; Waltham, MA, USA) employed in these reactions were sourced from previously published studies and are detailed in Table 7 [23,25,28,31,34]. Subsequently, DNA fragments were examined by electrophoresis on agarose gels using Midori Green Advance DNA Stain (Nippon Genetics, Düren, Germany).…”
Section: Studied Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation